A teaching subject: composition since 1966 - Harris, Joseph, author; Utah State University Press, publisher (Colorado State University. Libraries, 2012)
Reviewing the last 50 years of the development of writing studies as a discipline through five key ideas, Harris unfolds a set of issues and tensions that continue to shape the teaching of writing today.--Provided by publisher.
New edition.
Keywords: English language -- Composition and exercises -- Study and teaching; English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching